2021
DOI: 10.30827/arenal.v28i2.8812
|View full text |Cite
|
Sign up to set email alerts
|

Una aproximación al modelo corporal de santidad contrarreformista a través de la vida de Juana de la Cruz y otras santas franciscanas

Abstract: Este trabajo se propone demostrar cómo el cuerpo de las mujeres que aspiraron a ser santas durante la Edad Media y la Temprana Edad Moderna puede comprenderse como un espacio discursivo sociocultural performativo. Un cuerpo que se convierte en una intersección textual en la que los agentes que participan en el proceso comunicativo son capaces de (re)construir, (re)negociar, (re) significar y (re)interpretar este con el objeto de establecer los parámetros en que la santidad deseada debe ser ratificada. Para ell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a European study that assessed COVID-19 severity and morality in 697 patients with hematologic malignant neoplasms, a 33% mortality rate was observed and higher rates of severe disease and death in patients with leukemia were reported. 32 In the present study, among patients with solid tumors, those with lung, gastrointestinal (noncolorectal), and central nervous system tumors had worse outcomes. Higher mortality and increased risk of severe COVID-19 infection have been reported in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 54%
“…In a European study that assessed COVID-19 severity and morality in 697 patients with hematologic malignant neoplasms, a 33% mortality rate was observed and higher rates of severe disease and death in patients with leukemia were reported. 32 In the present study, among patients with solid tumors, those with lung, gastrointestinal (noncolorectal), and central nervous system tumors had worse outcomes. Higher mortality and increased risk of severe COVID-19 infection have been reported in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 54%
“…COVID-19, which is due to infection with SARS-CoV-2, results in poor outcomes in patients with hematologic cancers (approximately 40% mortality rate). 1,2 The efficacy of anti-SARS-CoV-2 mRNA vaccines has been successfully demonstrated in healthy populations 3 and also has been reported in immunocompromised patients. Recently, we showed that a first injection of the BNT162b2 (Pfizer-BioNTech) vaccine induced an antibody response in 55% of 112 allogeneic hematopoietic stem cell transplant (HSCT) recipients.…”
Section: Introductionmentioning
confidence: 98%